UNLOCKING INDUSTRIAL GROWTH IN WEST AFRICA: HOW FINANCIALIZATION AND TECHNOLOGICAL INNOVATION SHAPE THE FUTURE - Oluwafemi Emmanuel ADEWUMI; Sodiq Olaiwola Jimoh; Muftah Abdul Shitu (Malete Journal of Accounting and Finance)
This study examines the moderating effect of technological innovation on the relationship between financialization and industrial output growth in West Africa. Despite the critical role of innovation in industrial transformation, the region faces barriers such as limited capital, poor infrastructure, and skill shortages. Using data from 16 West African countries and grounded in Kaldor’s Theory of Economic Growth, the study employs panel unit root tests and ARDL cointegration analysis to explore long-run relationships among financialization, technological innovation, government effectiveness, human capital, and trade openness. Results show that financialization has a negative and statistically significant effect on industrial output growth, reflecting a preference for short-term financial gains over productive investment. Technological innovation, while statistically significant, has only a marginal positive effect, and its moderation with financialization is negative and insignificant. Notably, a 1% increase in technological innovation is linked to a 2.39 percentage point decline in industrial output growth, challenging conventional assumptions. The study concludes that financialization undermines industrial development and limits the benefits of technological innovation. It recommends policy measures such as tax incentives, mandated industrial lending, financial regulation, R&D support, and workforce training to promote long-term investment, enhance technological adoption, and boost industrial output in West Africa.